Translation, adaptation and testing of an emergency care satisfaction scale in Swedish pediatric emergency departments - Anne Wennick (BMC, 2021)
Abstract Background Pediatric healthcare today shows a rising demand for research focusing on children’s perspectives on and consumer satisfaction with the nursing care they receive. Therefore, the purpose of this study was to translate and adapt the Consumer Emergency Care Satisfaction Scale (CECSS), a paper-based, self-administered 19-item questionnaire originally developed in the United States and targeted towards adults, and then test the new version in Swedish pediatric emergency departments. Methods The study was designed with a two-phase approach. Firstly, a forward–backward translation of the CECSS, involving expert consensus, was performed, and then the questionnaire was adapted for children aged 10–18 and assessed for face and content validity. Secondly, the translated and adapted questionnaire was tested with a clinical sample for construct validity, internal consistency, and reliability. This last aspect was assessed using a structured telephone interview 7–10 days after the participant visited a pediatric emergency department. All children participating in this study gave their assent (< 15 years) or consent (≥ 15 years), and their guardian’s written informed consent was also obtained. Results The paper-based, self-administered 19-item Swedish version of the CECSS was tested on a clinical sample consisting of 203 nonurgent children (boys: n = 109, 53.7 % and girls: n = 94, 46.3 %) between 10 and 18 years (mean age 13.8, SD 2.29). The factor analysis revealed three factors that explain 63.1 % of the total variation in the 15 items. The Cronbach’s alphas for the three dimensions (caring, teaching, and clinical competence) varied between 0.79 and 0.88. The intraclass correlation coefficient (ICC) for the entire Swedish version of the CECSS was 0.58, and the ICCs for the three dimensions varied between 0.56 and 0.71. Conclusions The results show that the developed Swedish Pediatric Consumer Emergency Care Satisfaction Scale (p-CECSS-S) is a valid, stable and easy-to-use-questionnaire that can be used to assess children’s satisfaction with nursing care.